2016
DOI: 10.1007/s00204-016-1801-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phase I metabolism on uptake, oxidative stress and genotoxicity of the emerging mycotoxin alternariol and its monomethyl ether in esophageal cells

Abstract: Studies on the genotoxicity of Alternaria mycotoxins focus primarily on the native compounds. Alternariol (AOH) and its methyl ether (AME) have been reported to represent substrates for cytochrome P450 enzymes, generating hydroxylated metabolites. The impact of these phase I metabolites on genotoxicity remains unknown. In the present study, the synthesis and the toxicological effects of the metabolites 4-hydroxy alternariol (4-OH-AOH) and 4-hydroxy alternariol monomethyl ether (4-OH-AME) are presented and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
1
28
0
1
Order By: Relevance
“…AOH is known for its genotoxicity [ 118 ]. However, the phase I metabolites, 4-OH-AOH and 4-OH-AME, had minor effect compared to AOH or AME in topoisomerase inhibition and DNA strand-breaking effects [ 174 ]. Phase II metabolism includes conjugation with glucuronic acid and sulfate [ 119 ].…”
Section: Biotransformation Of Mycotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…AOH is known for its genotoxicity [ 118 ]. However, the phase I metabolites, 4-OH-AOH and 4-OH-AME, had minor effect compared to AOH or AME in topoisomerase inhibition and DNA strand-breaking effects [ 174 ]. Phase II metabolism includes conjugation with glucuronic acid and sulfate [ 119 ].…”
Section: Biotransformation Of Mycotoxinsmentioning
confidence: 99%
“…( A ): Demethylation; ( B , C , H ): Hydroxylation; ( D , I ): Methylation; ( E , F ): Sulfation, glycosylation, and glucuronidation; ( G ): Epoxide reduction. CYP: Cytochrome P; and UGTs: Uridine 5′-diphospho-glucuronosyltransferase [ 71 , 117 , 121 , 172 , 173 , 174 , 177 , 178 , 179 , 180 , 181 ].…”
Section: Figurementioning
confidence: 99%
“…Moreover, Sarkanj et al (2018) reported AOH (up to 0.2 ng/mL) for the first time in human urine samples as new biomarkers of exposure. Catechols formed by hydroxylation of AOH and AME may be further methylated by catechol-O-methyltransferase (Pfeiffer et al 2007;Tiessen et al 2017), while AME was also reported to be demethylated by microsomes of rat, human, and porcine liver (Pfeiffer et al 2007). However, AOH and AME are thermally and chemically rather stable in food matrices and therefore persistent during food processing (Estiarte et al 2018;Siegel et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fleck et al [47] reported that AOH-induced reactive catechols react covalently with DNA forming depurinating adducts at the N-7 of guanine and the N-3 of adenine. Tiessen et al [48] added that AOH exposure induced complex distributions of γH2AX histones which are paramount biomarkers of DNA double strand breaks (DSBs) and strong indicator that AOH-induced DSBs are important triggering signals for G2 arrest and autophagy [49]. AOH has been proved as a DNA topoisomerase poison with certain selectivity for its IIa isoform [50].…”
Section: Discussionmentioning
confidence: 99%